2021
DOI: 10.1590/1982-0224-2019-0134
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic change in the diet of Semaprochilodus insignis (Characiformes: Prochilodontidae) during migration between two limnologically distinct environments in the Amazon Basin

Abstract: Semaprochilodus insignis is an Amazonian migratory fish species, moving in large shoals between white- and black-water rivers. It has long been classified as a detritivorous fish. However, it is possible that the trophic plasticity of S. insignis could be higher than previously assumed. The objective of this study was to investigate the relative contributions of autotrophic energy sources to the diet of S. insignis in the Negro and Solimões rivers and to determine if the species undergoes an ontogenetic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…2017 and Jan. 2017 might be affected by contamination by calcium in the rocks they were growing on. The δ 13 C values of periphyton in this study were similar to those reported by previous studies [27]. Previous studies demonstrate the importance of periphyton for shrimp growth, including postlarvae.…”
Section: Physical and Chemical Characteristics Of Watersupporting
confidence: 91%
See 1 more Smart Citation
“…2017 and Jan. 2017 might be affected by contamination by calcium in the rocks they were growing on. The δ 13 C values of periphyton in this study were similar to those reported by previous studies [27]. Previous studies demonstrate the importance of periphyton for shrimp growth, including postlarvae.…”
Section: Physical and Chemical Characteristics Of Watersupporting
confidence: 91%
“…In river ecosystems, periphyton is the main carbon source for consumers, [26], there were studies showing that the δ 13 C values of periphyton are relatively low, ranging from −37.34‰ to −19.19‰ [27][28][29], and have noted that these values can be affected by other primary producers in the water along the rock belt [30][31][32]. The δ 13 C value of periphyton is significantly related to their growth environment.…”
Section: Physical and Chemical Characteristics Of Watermentioning
confidence: 99%
“…Thus, in addition to ecological importance, omnivores are historically important for commercial fisheries in the region, with species such as tambaqui and matrinxã being among the largest known landings (Gonçalves et al., 2021; Goulding et al., 2019). Strategies for exploring food resources available in different periods of the hydrological cycle could be through migratory behavior and ontogenetic changes, thus making it difficult to define the feeding pattern of Amazonian fish species (Soares et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, the concept of the isotopic niche was proposed, in which the axes of the multidimensional space are isotopic values that record bionomic and scenopoetic ecological information (Newsome et al ., 2007). Several authors have demonstrated that the isotopic niche is an important tool for exploring resource partitioning (Alves et al ., 2020), ontogenetic dietary shifts (Soares et al ., 2021) and niche overlap (Pennock et al ., 2021). This tool is especially useful for predator species, where the isotopic niche can provide a quantitative estimate of the energetic contribution and trophic level of prey species.…”
Section: Introductionmentioning
confidence: 99%